2015 Sustainability Review - World Bank (Washington, DC, 2015)
The 2015 Sustainability Review provides insights into activities undertaken to manage environmental, social, and economic impacts in the World Bank’s internal business operations. The content and data in this document relate to the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA), together the World Bank.